Lanthanoid complexes supported by retro-Claisen condensation products of ß-triketonates. - Abad Galán, L.; Sobolev, A.; Zysman-Colman, E.; Ogden, Mark; Massi, Massimiliano (R S C Publications, 2018)
ß-Triketonates have been recently used as chelating ligands for lanthanoid ions, presenting unique structures varying from polynuclear assemblies to polymers. In an effort to overcome low solubility of the complexes of tribenzoylmethane, four ß-triketones with higher lipophilicity were synthesised. Complexation reactions were performed for each of these molecules using different alkaline bases in alcoholic media. X-ray diffraction studies suggested that the ligands were undergoing decomposition under the reaction conditions. This is proposed to be caused by in situ retro-Claisen condensation reactions, consistent with two examples that have been reported previously. The lability of the lanthanoid cations in the presence of a varying set of potential ligands gave rise to structures where one, two, or three of the molecules involved in the retro-Claisen condensation reaction were linked to the lanthanoid centres. These results, along with measurements of ligand decomposition in the presence of base alone, suggest the solvent used will modulate the impact of the retro-Claisen condensation in these complexes.